Assessment of Health, Safety and Environmental Risks of Zahedan City Gasoline Stations - Far, S. Y.; Mirzaei, R.; Katrini, M. B.; Haghshenas, M.; Sayahi, Z. (Engineering, Technology & Applied Science Research, 2018)
The purpose of this study was to assess the risk and determine the health, safety and environmental status of fuel stations in Zahedan. In this study, failure mode and effects analysis (FMEA) method was used for risk assessment in accordance with the HSE guidelines, national and international standards and laws. In this cross-sectional study, 2 governmental stations and 6 active private stations were evaluated after the necessary coordination with the relevant units. As a result of risk assessment, 27 health risks, 55 safety risks and 22 environmental risks were identified. From among all the identified risks, 67 risks had a Risk Priority Number (RPN) of less than 91, 31 risks had an RPN ranging between 91 and 201, and 6 risks had an RPN of over 201. The findings of the study indicated that compliance with the HSE requirements was 51.85%, in the area of health, 47.57% in the area of safety and 27.45% in the environmental area. Overall compliance with the HSE requirements was 42.54%. In order to distribute fuel considering health, reducing risk and increasing compliance with the requirements for safety improvement, health and environmental conditions of fuel supplies are essential.